Sales of private firms and the role of CEO compensation - Burns, Natasha; Jindra, Jan; Minnick, Kristina (Journal of Corporate Finance, 2017)
We analyze the relation of private firms' CEO compensation with the probability of sale of a firm and its valuation at the time of the sale. Specifically, we study whether equity-based remuneration is consistent with compensating the CEO for effort related to selling the private firm, or with compensating for the illiquidity of the equity-based compensation for private firms. Using a sample of large private firms with public filings, we find that CEOs of IPO and acquired private firms have higher total and equity-based compensation than CEOs of firms that remain private. We also show that CEO compensation is positively related to the valuation premium of IPOs versus acquired firms.